La innovación y el emprendimiento en los estudiantes de la carrera de Ingeniería Comercial de la Universidad Nacional de Chimborazo - Rojas Tite, Marco Javier (2021)
This research work, that was carried out at the Universidad Nacional de Chimborazo to the students of the Commercial Engineering Career, Business Administration, deals with the study of how innovation influences the entrepreneurship of the students of the career, identifying the role and the influence of the professor in the relationship of innovation and entrepreneurship and the degree of acceptance of the students. In the first part of the research work, topics such as the introduction have been examined, the problems faced by the students of the career were analyzed as well as its current situation. After that, both, general and specific objectives were formulated to help determine each of the problems that students deal with within the topics of innovation and entrepreneurship. In addition, the state of the art consists of the antecedents, theoretical foundation, in this, 2 research units were addressed and they are described as follows: Unit I: Innovation. Unit II: Entrepreneurship. Within the methodological framework, to develop the research, the Hypothetical - Deductive method was used, and a non-experimental research design, within the population, the total number was taken into account, the sample was made up by 105 students, in addition, the techniques for data collection were used, such as the survey in order to obtain information, analysis and interpretation of results. After that, the information was processed using the SPSS Stactics statistical software with which, the analysis, discussion of results and verification of the hypothesis were carried out. And, as the last step for this research, the conclusions and recommendations were stated, the bibliography and corresponding annexes of the research are also attached.